2022
DOI: 10.1002/jaba.938
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of behavioral data with effect sizes and statistical significance tests

Abstract: This article describes the use of statistical significance tests and distance‐based effect sizes with behavioral data from single case experimental designs (SCEDs). Such data often are interpreted only with visual analysis. However, a growing movement in the field is to quantify results to improve decision‐making and communication across studies and sciences. The goal of the present study was to assess the agreement between visual analysis and various statistical tests. We recruited visual analysts to judge 16… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…With respect to the small yet statistically significant effect observed in overall sound intensity, what remains less clear is whether such a change could be viewed as clinically significant (Ranganathan et al, 2015). Certainly, there has been increased support for the use of inferential statistics in assessing the effects of interventions within applied behavior analytic research (Costello et al, 2022; Fisher & Lerman, 2014; Kazdin, 2021). In addition, past research has documented the noise levels observed in canine shelter environments, which can regularly exceed 100 dB (Coppola et al, 2006; Sales et al, 1997) and result in measurable hearing loss for dogs (Scheifele et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the small yet statistically significant effect observed in overall sound intensity, what remains less clear is whether such a change could be viewed as clinically significant (Ranganathan et al, 2015). Certainly, there has been increased support for the use of inferential statistics in assessing the effects of interventions within applied behavior analytic research (Costello et al, 2022; Fisher & Lerman, 2014; Kazdin, 2021). In addition, past research has documented the noise levels observed in canine shelter environments, which can regularly exceed 100 dB (Coppola et al, 2006; Sales et al, 1997) and result in measurable hearing loss for dogs (Scheifele et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Tau may be used across SCD types and do not require a minimum number of replications within or across participants to produce viable coefficients (i.e., between‐case parametric measures; Dowdy et al, 2021). This advantage may be, in part, the reason that ‘Tau and it's variations [i.e., Tau‐U, Tau‐BC] are the leading statistic for identifying the presence or absence of an effect for [single‐case experimental designs]’ (Costello et al, 2022, p. 3). While many advantages may be associated with Tau, specifically Tau‐U, remaining limitations, including the fact that Tau‐U estimates are inflated and not bound between −1 and 1, may make baseline corrected Tau (Tau‐BC) the optimal option for the current study's purpose (Tarlow, 2017).…”
Section: Methodsmentioning
confidence: 99%